2022
DOI: 10.1158/2767-9764.crc-22-0256
|View full text |Cite|
|
Sign up to set email alerts
|

A Ketogenic Diet in Combination with Gemcitabine Increases Survival in Pancreatic Cancer KPC Mice

Abstract: Pancreatic ductal adenocarcinoma (PDAC) continues to be a major health problem. A ketogenic diet (KD), characterized by a very low carbohydrate and high fat composition, has gained attention for its anti-tumor potential. We evaluated the effect and mechanisms of feeding a strict KD alone or in combination with gemcitabine in the autochthonous LSL-KrasG12D/+; LSL-Trp53 R172H/+; Pdx1-Cre (KPC) mouse model. For this purpose, both male and female pancreatic tumor-bearing KPC mice were allocated to a control diet (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 50 publications
(57 reference statements)
0
19
0
Order By: Relevance
“…high-fat/protein diet, increases blood levels of the ketone body β-hydroxybutyrate and can improve the efficacy of ICB [21,22]. In one study, KD in combination with gemcitabine has shown to increase by 42% the overall median survival in KPC mice, a model of pancreatic ductal carcinoma.…”
Section: Shaping the Microbiome With The Dietmentioning
confidence: 99%
See 2 more Smart Citations
“…high-fat/protein diet, increases blood levels of the ketone body β-hydroxybutyrate and can improve the efficacy of ICB [21,22]. In one study, KD in combination with gemcitabine has shown to increase by 42% the overall median survival in KPC mice, a model of pancreatic ductal carcinoma.…”
Section: Shaping the Microbiome With The Dietmentioning
confidence: 99%
“…The diet has been shown to be one of the most powerful modulators of microbiota composition. Two recent studies in mice have shown that the ketogenic diet (KD), a low‐carbohydrate, high‐fat/protein diet, increases blood levels of the ketone body β‐hydroxybutyrate and can improve the efficacy of ICB [21, 22]. In one study, KD in combination with gemcitabine has shown to increase by 42% the overall median survival in KPC mice, a model of pancreatic ductal carcinoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, hepatic metabolism serves a major role in substrate availability and metabolic alterations during fasting or with fasting mimicking diets such as KDs, especially when given simultaneously with chemotherapy (8)(9)(10). It was recently reported that a KD enhances the anticancer effect of gemcitabine (2',2'-difluoro-2'-deoxycytidine), improves survival and mitigates cachexia in LSL-Kras LSL-G12D/+ Trp53 R172H/+ Pdx-1-Cre (KPC) tumor-bearing mice (11,12). Although additional evidence on the efficacy of KDs in combination with chemotherapy exists (4,13), little is known regarding the safety of KDs with or without concomitant treatment with gemcitabine, an antineoplastic drug commonly used in pancreatic cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In the original version of ( 1 ), there is an error in the abstract. The macronutrient composition of both the ketogenic and control mouse diets was incorrectly reported in the abstract.…”
mentioning
confidence: 99%